PERSPEKTIF MORFOLOGI DERIVASIONAL DAN INFLEKSIONAL PADA VERBA BERAFIK BAHASA INDONESIA - Ermanto, Ermanto (Universitas Muhammadiyah Surakarta, 2008)
In many languages in the world, there are two tendencies of word formation: (1) word formation which changes the lexical identity (derivation), and (2) word formation which keeps the lexical identity (inflection). The morphology process in verbs in Indonesian is divided into affixational derivation, inflectional derivation. The affixational derivation process which derive the verb lexemes uses deriva- tional affixes, meanwhile the affixational inflection process which derive the word forms (grammatical words) uses inflection affixes. The function of derivational affix is to derive the intransitive verbs and/or to derive the transitive verbs. The function of inflectional affix is to derive the grammatical words.Â Key words: morphology process, derivation, inflection, verb, dan leksem.Â Â